2015
DOI: 10.1002/sia.5799
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies of magnesium oxide‐based catalysts modified with X2 or MgX2 (X = Br, I)

Abstract: The introduction of a halide (Br, I) onto MgO leads to obtaining catalysts whose catalytic activity in transfer hydrogenation of acrolein with ethanol is significantly higher than that of unmodified MgO. In data found in literature, there is no concise view on how the modification of the surface of MgO with a halide affects its surface properties. Although most of the literature studies indicate a dependence of activity on the initial halide‐containing compound and type of halide, no study comprising both thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In fact, it is one of the strongest solid bases . As our previous studies have shown, the modification of the surface with the deposition of bromine or iodine by impregnation of the MgO with a methanol solution of the halide precursor can influence the strength of active sites, as well as introduce new types of active sites . The iodine‐modified catalysts exhibit narrow XPS Mg 2p signals, whereas those of unmodified MgO and bromine‐modified catalysts exhibit wide signals, which is in line with the fact that iodine is more selective than bromine and hence has a less varied chemical environment.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…In fact, it is one of the strongest solid bases . As our previous studies have shown, the modification of the surface with the deposition of bromine or iodine by impregnation of the MgO with a methanol solution of the halide precursor can influence the strength of active sites, as well as introduce new types of active sites . The iodine‐modified catalysts exhibit narrow XPS Mg 2p signals, whereas those of unmodified MgO and bromine‐modified catalysts exhibit wide signals, which is in line with the fact that iodine is more selective than bromine and hence has a less varied chemical environment.…”
Section: Introductionsupporting
confidence: 60%
“…When the counterion is changed from potassium to hydrogen, the activity of thus obtained system is significantly higher, ie, 2.93. Values of 3.30 and 3.50 were obtained for MgO‐MgI 2 and MgO‐I 2 , respectively (data taken from our previously published results). The modified catalysts contain 0.3% to 0.6% of iodine on the surface as determined by XPS analysis.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations